Generate a Secured Multi-Purpose Code from Fingerprint Images (Al-Mansour Journal, 2022)
Extracting minutia and other features from fingerprint images is one of the most important steps in automaticfingerprint identification and classification. This paper proposes a method for the generation of long and securecode that may be used for multi-purpose applications, such as ATM, coded door locks and other security measures.The method consists of two phases; the first phase is carried out using fingerprint image enhancement andthinning. The second phase consists of extracting minutia, ridge ending, bifurcation and all other features in order toproduce initial pattern. Finally, the multi-purposes secure code is generated by applying the one-way MD5 hashfunction on that pattern. The achieved results are discussed for security improvement. The proposed technique also shows considerable improvement in the minutia detection process in terms of both efficiency and speed.
Keywords: Fingerprint matching; Image; reference point; code generation; embedded system